2021
DOI: 10.1186/s13031-021-00379-0
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent access to health services in fragile and conflict-affected contexts: The case of the Gaza Strip

Abstract: Background Enjoyment of physical and mental health is not only recognized as a human right but also as an integral part of development, as reflected in Sustainable Development Goal 3 – to ensure healthy lives and promote well-being for all at all ages. The rapid physical and psychosocial changes that take place during adolescence have a strong influence on the rest of a person’s life course, so investments in adolescent health services constitute a unique opportunity to reap inter-generational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…Reading these papers together as a "body of literature" affords powerful insights into how communities are navigating challenges and barriers, often with few external resources but with their own "everyday ingenuities" [35]. The papers captured and shared a wide range of voices in the form of vivid quotes, from the 14-year-old girl from the Gaza Strip who described her marriage as "suffocation" [14] to the worker from Ghizou, China who wryly observed "If you don't have money don't take the bus. It's humiliating to be thrown off" [46] (p. 193).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reading these papers together as a "body of literature" affords powerful insights into how communities are navigating challenges and barriers, often with few external resources but with their own "everyday ingenuities" [35]. The papers captured and shared a wide range of voices in the form of vivid quotes, from the 14-year-old girl from the Gaza Strip who described her marriage as "suffocation" [14] to the worker from Ghizou, China who wryly observed "If you don't have money don't take the bus. It's humiliating to be thrown off" [46] (p. 193).…”
Section: Discussionmentioning
confidence: 99%
“…Not surprisingly, many research participants reported difficulties in accessing health care, including financial barriers, drug shortages and lack of transport [8][9][10][11][12][13]. Six studies also cited shortages of health-care workers and unfriendly interactions with health-care providers as barriers to accessing health care [11,[14][15][16][17][18]. Masong et al [19] found that marginalised community members experienced a lack of trust in government-backed schistosomiasis treatment and prevention programmes, a further barrier to accessing health care and achieving SGD 3.8 ("access to quality essential health-care services").…”
Section: Good Health and Well-beingmentioning
confidence: 99%
“…However, expropriation of land has created a condition of dispossession that has further compromised Palestinians’ abilities to withstand the deliberate de-development strategy pursued by Israel, through punitive economic and military policies. Israel still has overall sovereignty of Gaza, controlling its borders, economy, movement of goods and people, electricity, communications, and security—the key aspects of Palestinians’ lives [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nearly 40% of total health expenditure in Gaza is out-of-pocket [ 8 ]. Despite that health insurance coverage is widespread (more than 90% of households), still it does not meet people’s needs; few medicines are covered by insurance (if available at all), and there are limited specialist services and long waiting lists [ 4 ]. While people are ordinarily able to access basic health services, access becomes challenging during renewed outbreaks of conflict, and access to advanced services outside Gaza (such as radiotherapy, advanced cardiac and neurosurgery) remains limited [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation